2012
DOI: 10.1186/1744-9081-8-33
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in mathematics anxiety and the relation to mathematics performance while controlling for test anxiety

Abstract: BackgroundMathematics anxiety (MA), a state of discomfort associated with performing mathematical tasks, is thought to affect a notable proportion of the school age population. Some research has indicated that MA negatively affects mathematics performance and that girls may report higher levels of MA than boys. On the other hand some research has indicated that boys’ mathematics performance is more negatively affected by MA than girls’ performance is. The aim of the current study was to measure girls’ and boys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

58
261
10
21

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(377 citation statements)
references
References 76 publications
58
261
10
21
Order By: Relevance
“…The results of this study are consistent with those of the authors (Strand, 2003;Devine, Fawcett, Szucs & Dowker, 2012, PISA, 2012 explaining that women show more anxiety toward mathematics than its counterpart.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study are consistent with those of the authors (Strand, 2003;Devine, Fawcett, Szucs & Dowker, 2012, PISA, 2012 explaining that women show more anxiety toward mathematics than its counterpart.…”
supporting
confidence: 92%
“…They also demonstrated that there are significant differences between students from different areas of knowledge. Devine et al (2012) showed that high school students experience anxiety toward mathematics and showed that women report more anxiety toward mathematics and lower academic achievement than men.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In another research with 10th grade students Karimi and Venkatesan (2009) examined the relationship between mathematics anxiety and performance. Researchers stated negative significant correlation between mathematics performance and anxiety parallel to the other research studies in the literature (Devine, Fawcett, Szucs, Dowker, 2012;Hembree, 1990;Ma, 1999). Based on the above literature we could deduce that although several research studies have been carried out regarding mathematics anxiety, little attention was given to younger students (Bonnstetter, 2007).…”
Section: Mathematics Anxietymentioning
confidence: 73%
“…MA thus seems to have serious consequences, not only in the short term (on math performance at school), but also in the long term, adversely influencing an individual's choice of career, type of occupation and professional growth in adulthood (Ashcraft & Ridley, 2005;Beasley, Long, & Natali, 2001;Chipman, Krantz, & Silver, 1992;Hembree, 1990;Ho et al, 2000). Concerning gender differences, the findings generally suggest that females suffer from MA more than males (see Else-Quest, Hyde, & Linn, 2010; and see Devine, Fawcett, Szu cs, & Dowker, 2012, for a short review), and that women are consequently less likely to seek opportunities for math problem solving, and they tend to avoid math-related activities (Balo glu & Kocak, 2006;Else-Quest et al, 2010;Jain & Dowson, 2009;McGraw, Lubienski, & Strutchens, 2006;Rubinsten, Bialik, & Solar, 2012).…”
Section: Thinking and Reasoningmentioning
confidence: 99%